UFSW tool pin profile effects on properties of aluminium-steel joint. (October 2021) - Xu, Xinli; Zhang, Chunwei; Derazkola, Hamed Aghajani; Demiral, Murat; Zain, Azlan Mohd; Khan, Afrasyab
Abstract: Effects of underwater friction stir welding tool pin profiles were studied on mechanical properties of AA5182 alloy and St-12 steel dissimilar joint. For this purpose, frustum, triangle, cubic, and hexagonal pin profiles were selected. Thermal history, microstructure analysis, tensile strength, and hardness of joint lines were assessed. The obtained results indicated that due to the high cooling rate of water environment conditions, the presence of edges in the tool pin shape (triangle, cubic, and hexagonal) improves internal material flow. Also, edged pin profiles increase the generation of frictional heat, the thickness of Intermetallic Compounds (IMC), and mechanical interlocking at base materials' interface. The hexagonal pin profile had the most significant favourable influence on the aluminium-steel joint properties among selected tool profiles. The chemical composition of IMCs at the materials interface was FeAl3 and Fe2 Al5, and the thickest IMC was formed near 6.5 μm. According to the results, the joint's highest tensile strength was 69% of aluminium alloy strength, which was obtained with a hexagonal pin profile. Highlights: Effects of dissimilar underwater FSW tool pin profiles were studied on aluminum-steel joints. Relation between FSW tool pin profile and mechanical properties of AA5182 alloy and St-12 steel dissimilar joint evaluated. Thermal history, microstructure analysis, Intermetallic compounds, and hardness of joint lines were assessed.